At low doses ethanol maintains blood–brain barrier (BBB) integrity after hypoxia and reoxygenation: a brain slice study. (October 2013) - Peng, Changya; Li, William A; Fu, Paul; Chakraborty, Tia; Hussain, Mohammed; Guthikonda, Murali; Rafols, Jose A; Ding, Yuchuan
Abstract : Post-ischemia ethanol (EtOH) treatments have been shown to exhibit neuroprotective effects in stroke. However, the mechanisms underlying these effects and those on blood–brain barrier (BBB) integrity have yet to be elucidated. In the present study, we determined whether administering differing concentrations of EtOH alter the expressions of BBB integral proteins, including aquaporins-4 and -9 (AQP-4, AQP-9), matrix metallopeptidases-2 and -9 (MMP-2, MMP-9), zonula occludens-1 (ZO-1), and basal lamina (laminin). We employed an organotypic brain slice culture model that utilizes oxygen–glucose deprivation followed by reoxygenation (OGD/R). Brain slices were obtained from 10-day-old Sprague–Dawley rats and divided into the following five groups ( n  =  8 subjects per group): (1) control, (2) hypoxia (OGD/R), no EtOH, (3) OGD/R and 10 mM EtOH, (4) OGD/R and 30 mM EtOH, and (5) OGD/R and 90 mM EtOH. To assess BBB integrity, levels of AQPs, MMPs, ZO-1, and laminin were determined by Western blot. Compared to control, OGD/R without EtOH significantly increased AQP-4, AQP-9, MMP-2, and MMP-9 levels, while decreasing ZO-1 and laminin levels. All EtOH concentration treatments (groups 3 through 5) significantly reduced the expressions of AQP-4, AQP-9, MMP-2, and MMP-9, compared to the OGD/R, non-alcohol treated slices. Furthermore, compared to the OGD/R without EtOH group, the 30 mM EtOH treatment significantly increased ZO-1 and laminin levels. In contrast, the 90 mM EtOH level neither enhanced the reduction in AQP and MMP levels nor increased ZO-1 or basal lamina expressions observed in the 30 mM treatment. In conclusion, at an optimal dose of 30 mM, EtOH improves the expressions of MMP-2, MMP-9, AQP-4, AQP-9, ZO-1, and basal laminin, previously altered by OGD/R. These effects may indicate a beneficial effect of EtOH on BBB integrity after stroke.